2019
DOI: 10.1016/j.physletb.2019.05.018
|View full text |Cite
|
Sign up to set email alerts
|

String breaking by light and strange quarks in QCD

Abstract: The energy spectrum of a system containing a static quark anti-quark pair is computed for a wide range of source separations using lattice QCD with N f = 2 + 1 dynamical flavours. By employing a variational method with a basis including operators resembling both the gluon string and systems of two separated static mesons, the first three energy levels are determined up to and beyond the distance where it is energetically favourable for the vacuum to screen the static sources through light-or strange-quark pair… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 69 publications
5
91
0
Order By: Relevance
“…The full mixing analysis with an enhanced spatial resolution as well as higher statistics is underway [20], utilizing a set of off-axis distances between 17a and 21.8a to ensure that we are able to map out the first as well as the second expected avoided level crossing.…”
Section: Results and Outlookmentioning
confidence: 99%
“…The full mixing analysis with an enhanced spatial resolution as well as higher statistics is underway [20], utilizing a set of off-axis distances between 17a and 21.8a to ensure that we are able to map out the first as well as the second expected avoided level crossing.…”
Section: Results and Outlookmentioning
confidence: 99%
“…with σ, χ and β standing for the string tension, the color Coulomb strength, and a constant fixing the origin of the potential respectively. On the other hand, unquenched (with gluon and lightquark fields) lattice QCD calculations [17,18] have shown that due to string breaking the association of the light field ground state with a QQ configuration holds only for small values of the relative QQ distance r ≡ jrj. When increasing r the QQ configuration mixes significantly with mesonmeson configurations.…”
Section: A Static Limitmentioning
confidence: 99%
“…In Fig. 1 we have represented graphically this situation for QQ and one meson-meson threshold (the representation for two meson-meson thresholds can be seen in [17,18]).…”
Section: A Static Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…The boundary conditions of the solutions (u(r), χ(r)) of the Schrödinger equation (50) can be read of from Eqs. (40), (41), (46) and (47) and are u(r) ∝ r for r → 0 (64) u(r) = 0 for r → ∞ (65) χ(r) ∝ r 2 for r → 0 (66)…”
Section: A S and T Matrix Poles In The Complex Energy Plane And Theimentioning
confidence: 99%